2015
DOI: 10.1080/2159256x.2015.1045115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of horizontal transmission on the stability of plasmids under different selection regimes

Abstract: In theory, plasmids can only be maintained in a population when the rate of horizontal gene transfer is larger than the combined effect of segregational loss and the decrease of fitness associated with plasmid carriage. Recent advances in genome sequencing have shown, however, that a large fraction of plasmids do not carry the genes necessary for conjugation or mobilization. So, how are so-called non-transmissible plasmids able to persist? In order to address this question, we examined a previously published e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Plasmids can promote bacterial survival in the presence of antibiotics, but, as we have seen, they can also impose a fitness cost when they enter a new bacterial host. The past few years have witnessed growing interest in the fitness effects of plasmids (21)(22)(23)(24)(25)(26)(27)(28)115), and some of the general principles underlying these effects are now beginning to be identified. However, we still are a long way from understanding the specific molecular basis of these costs or being able to predict plasmid fitness effects in a bacterial host.…”
Section: Challenges In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids can promote bacterial survival in the presence of antibiotics, but, as we have seen, they can also impose a fitness cost when they enter a new bacterial host. The past few years have witnessed growing interest in the fitness effects of plasmids (21)(22)(23)(24)(25)(26)(27)(28)115), and some of the general principles underlying these effects are now beginning to be identified. However, we still are a long way from understanding the specific molecular basis of these costs or being able to predict plasmid fitness effects in a bacterial host.…”
Section: Challenges In the Fieldmentioning
confidence: 99%
“…The idea underlying this hypothesis is that even if plasmids produce a cost when they first arrive in a new bacterial host, this cost could be alleviated over time through compensatory mutations in the plasmid and/or the host chromosome (20). In recent years, several studies have analyzed the molecular basis of the cost and compensation of plasmids in bacterial populations (21)(22)(23)(24)(25)(26)(27)(28), generating new models of the existence conditions of plasmids (22,24). These studies evaluate a number of selection, transfer, and compensation regimes that could explain plasmid survival in bacterial populations, and have revealed new evidence about the molecular mechanisms underlying the cost of and adaptation to plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the organisms present in wastewater are fast growing bacteria that have the capacity to adapt and become important vectors of ARGs (McGowan, 2006). Many bacterial species resistant to different clinically important antibiotics have been detected in wastewater influent, effluent and downstream environments (Zhang and Li, 2011;Peña-Miller et al, 2015;Keraita and Drechsel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The major health concern is also that farmers specifically prefer using these effluent contaminated water bodies as sources of water for irrigation. Studies have revealed high levels of microbiological contamination with antibiotic-resistant coliforms and pathogenic bacteria including the ARGs in wastewater and sludge used for agricultural purposes (Keraita and Drechsel, 2004;Rahube et al, 2014a;Peña-Miller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Essas diferentes vias pelas quais plasmídeos podem aumentar sua persistência, tais como interações entre plasmideo-plasmideo, plasmídeo-hospedeiro ou ambos, demonstram que existem múltiplos mecanismos no processo de estabelecimento de um plasmídeo em uma população bacteriana (LOFTIE-EATON et al, 2015;PENA-MILLER et al, 2015). .…”
Section: Inserções E Deleções Gênicasunclassified